Awareness about generic drug prescription amongst practitioners: a knowledge attitude practice survey at rural set up - Patil, Jyoti Ramchandra; Jaykare, Swapnil Chudaman; Motghare, Vijay Motiram; Padwal, Sudhir Laxmanrao; Deshmukh, Vinod Shivajirao (International Journal of Basic & Clinical Pharmacology, 2016)
Background: to evaluate the knowledge, attitude and practices regarding generic drugs prescription and the factors influencing it amongst practitioners at a rural set up. Methods: All the practitioners in the town, at both government and private settings were interviewed individually and the data was collected with the help of a self-administered, pre-validated and semi-structured questionnaire. Data were analysed to describe all variables and test any significant difference between the practitioners at government and private set-up. Results: The study included 97 practitioners from different affiliations with a response rate of 87.63%. Our survey showed that most of the practitioners (74.36%) were in favour of generic drugs substitution owing to their knowledge about generics. Majority of the practitioners (69.10%) were aware that both the brand and generic drugs are bioequivalent and that there exits significant price difference between them, yet, concerns regarding the manufacturing standards of the latter, prevented them from practicing generic substitution. Practitioners did not report a significant pressure from patients to prescribe either brand or generic drugs. Most practitioners (76.92%) had a positive attitude towards the government’s role in assuring the quality of generic drugs by improving manufacturing standards of these drugs. Conclusions: Although the practitioners were strongly in favour of generic substitution, concern regarding their quality standards is discouraging them from doing the same. The government can play a major role by improving the standard operating procedures for manufacturing the generic drugs thereby assuring the practitioners about their quality.